Evaluation of Online Patient Complaints Regarding City Hospitals in Türkiye During the COVID-19 Pandemic: A Content Analysis Study - Canan Çınar; Elif Erbay; Gökçen Çeliker; Ahmet Selçuk Yıldırım (The Beryl Institute, 2024)
The COVID-19 pandemic put tremendous pressure on healthcare systems worldwide, which led to heightened scrutiny of the medical services offered by hospitals. This article aims to evaluate complaints about city hospitals in Türkiye during the COVID-19 pandemic using the Healthcare Complaints Analysis Tool, which includes three main domains and seven problem categories. The complaints submitted by users on the site via "sikayetvar.com" were systematically collected. Document analysis was used as the data collection method, and 925 complaints were included in the analysis. The most common motive for complaining was "just to express" and problems occurred at the stage of admission, examination, and diagnosis, care on the ward. In this study, 1135 problems were reported, and resulting in a mean of 1.23 problems per complaint. The complaint domains were management (45%), relationship issues (31%), and clinical issues (24%). Within the clinical complaints domain, the most prevalent issues pertained to quality, with examination and monitoring emerging as the foremost concerns in the subcategory level. Considering complaints within the management domain, the category of institutional processes was most frequently mapped to the subcategory delay in access. Finally, complaints related to the relationships domain are mostly related to the categories of respect and patient rights and the subcategories of disrespect. Emphasizing patient feedback and complaint management, this study provides valuable insights for healthcare professionals and governments to enhance healthcare delivery during crises such as the COVID-19 pandemic.